2016
DOI: 10.1016/j.jobcr.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Nickel release from stainless steel and nickel titanium archwires – An in vitro study

Abstract: The highest amount of nickel was released from nickel titanium archwires, however, the quantity of nickel released from both NiTi and stainless steel archwires were not significant. The rate of nickel released was high within the first week and continued up to the first month after which the nickel content was stable in all the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
6
15
0
9
Order By: Relevance
“…The introduction of nickel–titanium alloys in 1971 for instance brought important progress for orthodontic treatment [ 2 ].Continuous long-term contact of orthodontic materials with teeth, gingivae, and the oral environment in general results in biodegradation of metals. Thereby, the patient is exposed to increased levels of metals and metal ions [ 13 , 23 ] beyond those resulting from dietary intake and other forms of exposure. The average daily intakes of nickel and chromium in food are, for instance, estimated to be 200–300 µg nickel/day [ 8 ] and 30–100 µg chromium/day [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of nickel–titanium alloys in 1971 for instance brought important progress for orthodontic treatment [ 2 ].Continuous long-term contact of orthodontic materials with teeth, gingivae, and the oral environment in general results in biodegradation of metals. Thereby, the patient is exposed to increased levels of metals and metal ions [ 13 , 23 ] beyond those resulting from dietary intake and other forms of exposure. The average daily intakes of nickel and chromium in food are, for instance, estimated to be 200–300 µg nickel/day [ 8 ] and 30–100 µg chromium/day [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, many metallic materials are chemically resistant to corrosion as long as a surface oxide layer is present. As soon as the oxide layer dissolves, the onset of surface corrosion starts [ 4 , 9 , 13 ]. The corrosion rate is influenced by the composition of the material, the chemical and thermal environment, the surface area, and the degree of surface smoothness [ 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such alloys are mainly composed of 68-80% nickel and 12-26% chromium but they also contain other elements in quantities varying from 0.1 to 14% [1,2]. Recent studies indicate an increased release of nickel from orthodontic appliances into the artificial saliva or into human salivary secretions [3][4][5]. Moreover, a few studies have demonstrated a positive correlation between the enhanced nickel concentration in oral mucosa cells released from fixed orthodontic appliances and DNA damage as well as increased number of apoptotic cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of MMPs that persist in gingival tissue after appliance removal can be associated with other local factors that may result from orthodontic treatment, such as metal release. Nickel, for example as a transition metal, has the ability to generate reactive oxygen species that could be linked to the activation of MMPs ( Golz et al, 2014 , Hussain et al, 2016 , Pazzini et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%